Local and Systemic Antibiotics in Peri-Implantitis Management: An Umbrella Review - Giovanni Boccia; Federica Di Spirito; Francesco D'Ambrosio; Maria Pia Di Palo; Francesco Giordano; Massimo Amato (MDPI AG, 2023)
The present umbrella review aimed to characterize the type and regimen of antibiotics administered locally and/or systemically, alone or in combination with surgical and nonsurgical treatments, for peri-implantitis and to evaluate and compare the associated clinical, radiographic, and crevicular peri-implant outcomes. The secondary objective was to determine the most effective antibiotic type, route of administration, regimen, and protocols (antibiotics alone or in combination with other approaches) for treating peri-implantitis. The study protocol, which was developed in advance under the PRISMA statement, was registered at PROSPERO (CRD42022373957). BioMed Central, Scopus, MEDLINE/PubMed, the Cochrane Library databases, and the PROSPERO registry were searched for systematic reviews through 15 November 2022. Of the 708 records found, seven reviews were included; three were judged of a critically low and four of low quality through the AMSTAR 2 tool. Locally administered antibiotics alone or as an adjunct to surgical or nonsurgical treatments for peri-implantitis showed favorable outcomes, albeit with limited evidence. The administration of systemically-delivered antibiotics in combination with nonsurgical or surgical treatments remained questionable. Local plus systemic antibiotics have not been shown to have durable efficacy. Due to the heterogeneity of reported antibiotic types, routes, regimens, and protocols, no definitive conclusions could be drawn regarding the most effective antibiotic use in treating peri-implantitis.